(untitled) (Ameghiniana, 2014)
Based on the analysis of climatic-environmental variables (particularly annual precipitations and hydric index), the possible paleonvironmental inferences derived from the rheid fossil record are restricted. The species distribution of this group of birds, influenced by the mentioned physical variables is discussed. Record of Pterocnemia pennata (d’Orbigny) at Paso Otero and Monte Hermoso, outside the area of present day distribution and where Rhea amiericana (Lynnaeus) actually lives, suggests an arid to semiarid clima te during the late Pleistocene-Holocene in those areas, with annuals precipitations up to 300 mm. A probable corologic change originated by a climatic deterioration during the late Pleistocene and the early Holocene, is postulated for the rheid population.